Impact of Health Information Systems on Organizational Management and the Evaluation of Disease Surveillance, Reporting, and Control in Three Selected States of Nigeria (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Introduction: Health information systems (HIS) play a pivotal role in organizing, managing, and evaluating disease surveillance, reporting, and control systems. In Nigeria, the effectiveness of these systems is critical for timely detection of outbreaks and implementation of control measures. However, systemic challenges such as inadequate funding, weak infrastructure, and poor data quality continue to hinder optimal performance.Objective: This study aimed to examine the effect of health information on the organization and management of disease surveillance, reporting, and control systems in three selected Nigerian states, identifying operational gaps and providing actionable insights for system strengthening.Method of Analysis: A descriptive cross-sectional design was employed, using a total enumeration of 160 respondents, including Medical Officers of Health and Disease Surveillance and Notification Officers (DSNOs) from all local government areas of Kwara, Osun, and Oyo States. Data were collected using validated structured questionnaires. Descriptive statistics such as frequencies, percentages, means, and standard deviations were used to analyze the data.Results: The findings revealed that 73.7% of respondents agreed that HIS revealed areas of epidemic occurrence, while 51.3% reported it provided effective data for measuring surveillance outcomes. A majority (82.7%) identified adequate funding as the most critical improvement factor, followed closely by accurate data collection (53.8%) and provision of information technology (47.4%). Additionally, HIS was reported to improve outbreak detection capacity (Mean = 3.21 ± 1.18) and facilitate disease prevention planning (Mean = 3.58 ± 0.50). Challenges such as irregular DSN form supply (67.9%) and inadequate manpower (50.5%) were highlighted as key impediments.Conclusion: The study concludes that health information significantly enhances the organization, reporting, and control of disease surveillance when adequately resourced and managed. Strengthening HIS through sustained funding, skilled manpower, technological integration, and improved supervision is essential for timely outbreak detection, evidence-based interventions, and overall disease control. These measures will enhance Nigeria’s readiness for both endemic and emerging public health threats.